2017
DOI: 10.1038/s41538-017-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Food-grade cationic antimicrobial ε-polylysine transiently alters the gut microbial community and predicted metagenome function in CD-1 mice

Abstract: Diet is an important factor influencing the composition and function of the gut microbiome, but the effect of antimicrobial agents present within foods is currently not understood. In this study, we investigated the effect of the food-grade cationic antimicrobial ε-polylysine on the gut microbiome structure and predicted metagenomic function in a mouse model. The relative abundances of predominant phyla and genera, as well as the overall community structure, were perturbed in response to the incorporation of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 73 publications
4
19
0
Order By: Relevance
“…Thus, the blood group A antigen in Coligo may affect the composition and function of microbial communities when fed to pigs. Moreover, recent studies demonstrated that dietary supplementation of ε-PL altered ileal microbiota structure and function in pigs [ 58 ] and fecal microbial community in mice [ 59 ]. ε-PL supplementation may promote the growth of beneficial microorganisms in the intestinal tract, therefore, reducing the proliferation of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the blood group A antigen in Coligo may affect the composition and function of microbial communities when fed to pigs. Moreover, recent studies demonstrated that dietary supplementation of ε-PL altered ileal microbiota structure and function in pigs [ 58 ] and fecal microbial community in mice [ 59 ]. ε-PL supplementation may promote the growth of beneficial microorganisms in the intestinal tract, therefore, reducing the proliferation of pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Irwin et al [14] showed on four probiotic strains that sulphites may in vitro inhibit bacterial growth at concentrations regarded as safe. Another group showed that antimicrobial biopolymer ε-polylysine could trigger transient compositional alterations in the mouse gut microbiome [15]. Our recent in vitro research on human gut isolates demonstrates that some gut microbes are highly susceptible to commonly used antimicrobial food additives.…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly applied agent is the cationic homopolymer ε-polylysine, certified as GRAS (Generally Recognized as Safe) and used in food processing in United States, Korea and Japan. Daily intake of ε-polylysine for 1, 5 and 9 weeks at the dose of 1.4 × 10 −6 g/g body weight in mice, which corresponds to the U.S. average per capita annual consumption of soft drinks, perturbs transiently both composition and function of gut microbiome [56]. Although the initial microbiota can be re-established at the end of the ε-polylysine-enriched-diet [56], this observation raises the possibility that prolonged intake of this agent may trigger permanent alterations of microbial composition and induce colitis.…”
Section: Effects Of Food Additives On Gut Homeostasismentioning
confidence: 99%